Wild swans : three daughters of China - Chang, Jung (New York : Anchor Books, 1992)
A Chinese woman chronicles the struggle of her grandmother, her mother, and herself to survive in a China torn apart by wars, invasions, revolution, and continuing upheaval, from 1907 to the present.
Includes index.
Keywords: Chang, Jung, -- 1952-; Women -- China; China -- Biography